Morphological, morphometric, and molecular characterization of Hepatozoon spp. (Apicomplexa, Hepatozoidae) from naturally infected Caudisona durissa terrifica (Serpentes, Viperidae) - Moco, Tatiana Cristina [UNESP]; da Silva, Reinaldo Jose [UNESP]; Madeira, Newton Goulart [UNESP]; Paduan, Karina dos Santos [UNESP]; Rubini, Adriano Stefani [UNESP]; Menezes Leal, Denise Dutra [UNESP]; O'Dwyer, Lucia Helena [UNESP] (Springer, 2012)
Hepatozoon spp. are the most frequent intracellular protozoa in snakes. Considering the variety of parasites infecting specimens of Caudisona durissa terrifica and the divergent data in literature where only two species, Hepatozoon romani and Hepatozoon capsulata, are described, the aim of this study was to morphologically, morphometrically, and molecularly characterize Hepatozoon spp. from some naturally infected specimens of C. durissa terrifica, and observe changes caused by these protozoa in parasitized erythrocytes. Four snakes were examined. Two of them had two morphological distinct gamonts, while the other two had only one type of gamont. The six distinct gamonts were provisionally named gamonts A, B, C, D, E, and F. Statistical analysis, however, confirmed the existence of only four parasite populations, those which were capable of inducing significant alterations in determined red blood cells variables. Attempts to infect Aedes aegypti and Culex quinquefasciatus mosquitoes were done for each snake specimen. Some mosquitoes became infected and oocysts were recovered and measured. The detection of Hepatozoon DNA was obtained with success but the molecular characterization was unable to differentiate species of the samples, with respect to the fragment studied.